Penilaian Ahli dalam Penyelesaian Sengketa - Muhana, Ahmad Fauzi Muhana (PT. AORSA ADIVISI KAKA, 2026)
Disputes are inevitable in today's complex legal world, and effective and efficient resolution is crucial to maintain legal certainty. In addition to litigation in the Courts, Alternative Dispute Resolution (APS) is becoming increasingly popular. This is because it offers faster, cheaper and more flexible solutions. One of the most popular methods in APS is expert judgment. Therefore, this research will comprehensively examine the definition, function, process, and advantages of expert judgment in the context of dispute resolution. Expert judgment generally involves one or more experts in a particular field to provide an objective evaluation and comprehensive analysis of the technical or complex issues at the heart of the dispute. In contrast to expert testimony in Court, expert assessment in APS serves more as an instrument to help the parties understand the specific aspects of the problem, facilitate negotiations, and reach a mutually beneficial consensus. In addition, this research aims to provide a clear and comprehensive insight into the strategic role of expert judgment in realizing effective and equitable dispute resolution in Indonesia.